The Effect of Hypnobreastfeeding on the Fluency of Mother's Milk (ASI) in Postpartum Mothers at the Leni Langsa Independent Maternity Home in 2022 - Niasty Lasmy Zaen (Institute of Computer Science (IOCS), 2022)
One of the reasons for the failure to provide exclusive breastfeeding is their perception of insufficient milk production so that they cannot breastfeed their babies optimally. The decrease in milk production in the first days after giving birth is triggered by a lack of stimulation of the hormones prolactin and oxytocin which play a very important role in the smooth production of mother's milk. One of the efforts made to improve the smoothness of breastfeeding is Hypnobreastfeeding. The purpose of this study was to determine the Effect of Hypnobreastfeeding on the Fluency of Breastfeeding in Postpartum Mothers at Leni Langsa Independent Maternity Homes in 2022 This type of research is experimental research with the research design used being Pre-Experimental with the One Group Pretest-Posttest approach. The population in this study were all postpartum mothers at the Leni Langsa Maternity Home in September 2022 as many as 14 respondents. sampling technique with purposive sampling obtained as many as 12 respondents. Bivariate data analysis used the Wilcoxon signed rank test. The results of this study indicate that the mean value of each is 2.9167 (Pre) and 5.5833 (Post). The results of statistical tests using the Wilcoxon test are known that the p value (0.001) < (0.05) means Ho is rejected. The conclusion of the study is that there is a significant effect of hypnobreastfeeding on the smoothness of breastfeeding in postpartum mothers at the Leni Langsa Maternity Home in 2022. It is recommended for midwives can apply hypnobreastfeeding in overcoming the inability of breastfeeding so that postpartum mothers can exclusively breastfeed without obstacles